Carved Islamic Caligraphy In Palembang: Interaction Study Of Religious Value And Local Wisdom - Husni Mubarat (INJECT (Interdisciplinary Journal of Communication), 2020)
This study is aimed at examining the interaction of religious values and local wisdom on carving Islamic calligraphy in Palembang. In addition, this study is also aimed at analyzing the interaction of forms and philosophies of carving, physical functions, aesthetic functions, and socio-cultural functions. The benefits of this research include, being able to know how the interaction of religious values and local wisdom on carving Islamic calligraphy in Palembang, can provide motivation for the community to uphold the values of the holy book of the Koran, and can introduce the traditional carvings of Palembang to the wider community. This study uses a qualitative method with a multi-disciplinary approach, such as communication, aesthetics, and socio-culture. The research results achieved are; the interaction of religious values and local wisdom in the carvings are intertwined with mutually adapting harmony, calligraphic forms, decorative forms, and golden colors as characteristic of Palembang's local colors and physical, aesthetic and socio-cultural functions in Islamic calligraphy engraving in Palembang.